Symbiogenesis, Biocapitalism, and Subversion in Tabish Khair’s The Body by the Shore - Roy, Binayak (SARE: Southeast Asian Review of English, 2024)
Tabish Khair’s The Body by the Shore explores the widening gulf between the Islamic and the non-Islamic world and the equation of the Muslims with a threatening germ in a futuristic setting. Symbiosis (be it mutualism, commensalism or even parasitism) subverts an essentialist concept of ‘individuality’; interprets evolution of life forms as a collaborative process and foregrounds the idea of the Gaia as very much a living being. Khair’s speculative post-pandemic novel narrative is a scathing attack on biocapitalism, xenophobia and the twin forces of profit and privatization. The technicalities of molecularization have reduced human life to a series of digital chromosomal codes facilitating innovative ways of commoditization of life and furthering biocapitalism. The dystopian vision articulated by Khair in the novel asks for an intervention from a different perspective. Stuart Murray’s reconceptualization of Foucault’s “open and dynamic” “self-self” relation would act as liberation from the reductionism of biotechnology and allow the human self to slough off the state of domination of biocapitalism and look forward to a zone of fluidity and creativity.